INTERVENCIÓN EDUCATIVA SOBRE INFECCIONES DE TRANSMISIÓN SEXUAL EN ADOLESCENTES DEL TERCER AÑO DE SECUNDARIA DEL COLEGIO “LOS JAZMINES DE NARANJAL” DE LIMA, 2014 - Silvia E. Segura Zuloaga; Juan P. Matzumura Kasano; Hugo Gutiérrez Crespo (Horizonte Médico, 2015)
Objective: Determine the effectiveness of an educational intervention in order to increase the knowledge about Sexually Transmitted Infections (STI) in third-grade adolescents of “Los Jazmines de Naranjal” High School. Material and Methods: A pre-experimental, prospective and longitudinal study with a sample of 95 adolescents. At the beginning based on a Pre-test, an inadequate level of knowledge about Sexually Transmitted Infections was verified, that test was divided in four dimensions (definition, signs and symptoms, transmission and prevention). An educational intervention was implemented, with six sessions, where active learning strategies were used, and with a Post-test at the end of this. Descriptive analysis, frequency distribution and percentages, and the Wilconxon Test, were used to determine the intervention effectiveness. Results: In the sample, the 56% and 44% were female and male respectively, the age range was from 12 to 17 years, and 11.3% of the females and 31.8% of the men were sexually active. As a result of the educational intervention, the portion of adolescents with high level of STI knowledge increased in the four dimensions (definition: 91%, transmission: 100%, signs and symptoms: 98%, prevention: 100%). Conclusions: The educational intervention improved the knowledge about sexually transmitted infections in adolescents. This improvement is statistically significant.